Financial Sector Assessment Program Update : Republic of Kazakhstan - Investment Opportunities for Pension Funds - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
The objective of this note is to put forward policy alternatives that could lead to improved management of pension fund assets in Kazakhstan. This note emphasizes prudence in the management of pension assets, given the social and fiscal importance of the pension sector. It also discusses different investment alternatives and development options for the domestic Kazakhstani capital market. The note aims to be realistic and pragmatic, based on the best professional judgment of the author.1 It is concluded that neither the regulators nor industry participants appear to fully appreciate the risks attached to the practice of focusing on short-term and high yield investments, which exposes pensioners to higher reinvestment and issuer risk. The recommendations are summarized in the last section of this note.